The Influence of Physical Education on the Socio-Emotional Development of Children in Elementary Schools SD Inpres Pa'baeng-Baeng Makassar City - Irwandi, Andi; Nurwidyayanti; Burhan; A.Rizal (International Journal of Applied Educational Research (IJAER), 2024)
This study aims to examine the influence of physical education on the social-emotional development of children at SD Inpres Pa'Baeng-Baeng, Makassar City. Using a quantitative research design with a quasi-experimental approach, as many as 60 students in grades IV and V were randomly divided into two groups: an experimental group that participated in a structured physical education program and a control group that participated in a standard physical education program. Data were collected through social-emotional development questionnaires, observations, and interviews before and after the implementation of the program. The results of the analysis showed that the experimental group experienced a significant improvement in social-emotional development compared to the control group (t = 3.45, p < 0.05). Observations and interviews supported these findings by showing improved positive social interaction, cooperative skills, and emotional management in the experimental group. These findings confirm that structured physical education can effectively improve children's social-emotional development and, therefore, should be integrated into the primary school curriculum. This study provides the basis for further research on the impact of physical education on other aspects of child development.